Feasibility of evaluating AI-enabled digital symptom monitoring in metastatic patients with NSCLC receiving pembrolizumab therapy: A German single-arm observational pilot study - Melissa L. Santorelli; Oliver Schmalz; Mathias Hoiczyk; David Heigener; Clemens Schulte; Markus Knott; Petra Hoffknecht; Joonas Vainio; Thomas Burke; Josephine M. Norquist; Sabine Riehl; Alexander Hildner; et al. (Digital Health)
Introduction Close symptom monitoring can benefit patients with metastatic nonsmall cell lung cancer (mNSCLC) receiving first-line therapy. Remote patient monitoring technologies, like the artificial intelligence (AI)-enabled Kaiku ® Health platform that allows oncology patients to report their health status in real-time to healthcare providers, may enhance patients’ treatment experience. Methodology The lung artificial intelligence-enabled digital solution pilot study (“Lung AID”) assessed the feasibility of future studies on Kaiku ® Health in patients with mNSCLC receiving first-line pembrolizumab in Germany. Patient engagement with Kaiku ® Health and practicality of collecting patient-reported outcomes (PROs) via the separate Lung AID EDC system were assessed by platform access rates. Kaiku ® Health access required one login, while Lung AID EDC access required submission of ≥1 PRO questionnaire. Post hoc analyses explored access by site experience with Kaiku ® Health. Results Over a 17-month enrollment period, 47 of 100 planned patients were enrolled in the study. Kaiku ® Health was accessed by 85.1% of patients, with higher engagement at experienced sites (96.2%). Only 38.3% accessed the Lung AID EDC system; 31.9% used both systems. Discussion High Kaiku ® Health access rates imply patient interest in remote digital monitoring for mNSCLC. However, recruitment challenges and use of a separate system to collect PRO data demonstrated difficulties in assessing the feasibility of these technologies in real-world settings. Our results highlight the need for streamlined patient monitoring tools and enhanced site and patient engagement strategies. Conclusion While definitive conclusions on future studies cannot be drawn, the study offers key insights into challenges that should be considered in future research.